Strategi Komunikasi PT. Magic Detailing Dalam Meningkatkan Kepuasan Konsumen - Lestari, Rizki Dwi (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Magic detailing is a company operating in the auto detailing sector. Founded in 2015 and has been running for ten years. Auto detailing or what is usually called a car salon focuses on maintaining and beautifying the appearance of vehicles, whether cars or motorbikes, so that they look much more perfect. Magic detailing is one of the trusted car salons in Medan city because the workmanship provided to consumers is quite good. Each company creates a communication strategy to increase consumer satisfaction and offers services that are attractive to consumers so that the company is able to survive and the business runs smoothly in tight business competition, so that the Magic Detailing company's goals are achieved. This type of research is qualitative research with descriptive presentation, using interview data collection techniques and data analysis techniques for data reduction, data presentation, and drawing conclusions. The research results show that PT Magic Detailing's Communication Strategy in Increasing Consumer Satisfaction is carried out by: Communicating directly with customers, providing the best service, using the best quality products, and the price of the products or services provided is relatively affordable.